Early Success Is Vital in Minimal Worksite Wellness Interventions at Small Worksites. (August 2015) - Ablah, Elizabeth; Dong, Frank; Konda, Kurt; Konda, Kelly; Armbruster, Sonja; Tuttle, Becky
Intervention . In an effort to increase physical activity, 15 workplaces participated in a minimal-contact 10, 000-steps-a-day program sponsored by the Sedgwick County Health Department in 2007 and 2008. Pedometers were provided to measure participants' weekly steps for the 10-week intervention. Method . Participants were defined as those who completed the preregistration survey and logged at least 1 week of results. Registrants were defined as those who completed a registration survey but did not log any weekly results. The primary dependent variable was whether or not participants achieved weekly success, as measured by achieving at least 70, 000 steps in a week. A secondary dependent variable was participants' number of steps each week during the weeks they logged results. Repeated measures logistic regression analysis was conducted to identify factors associated with weekly success. Results . Of the 2, 515 registrants, 1, 292 (51%) were participants. The average number of weeks of participation for this 10-week intervention was 5.6 weeks ( SD = 3.4). Those from small employers ( n < 750) were more likely ( OR = 2.0) than those from large organizations ( n > 750) to become participants. Participants who achieved at least 70, 000 steps in the first week of the intervention were 7.3 times more likely than participants who walked less than 70, 000 steps in the first week to achieve 70, 000 steps each week for all 10 weeks. Conclusions . Results from implementing a minimal-contact 10, 000-step intervention can be maximized by targeting small worksites and supporting employees to achieve 70, 000 steps in their first week.